Quality of life of occupants of old age homes of a northern Indian province - Kumar, Sanjay; Gupta, Anmol; Mazta, Salig Ram; Sharma, Deepak; Chamotra, Shaina; Chaudhary, Ankit (International Journal Of Community Medicine And Public Health, 2023)
Background: Although a physiological phenomenon, ageing has enormous bearing on all the dimensions of health. Against age-old tradition, India is also witnessing a rapid increase in nuclearization of families. Increase in old age homes (OAHs) has been proportional to rising number of admissions in such institutions. In order to understand the phenomenon in a holistic way, the present study evaluated the quality of life of occupants such facilities in state of Himachal Pradesh. Methods: A descriptive cross-sectional study was conducted to capture quality of life among the occupants of all seven OAHs of the State. Data was collected using World Health Organisation quality of life-Bref (WHOQOL-Bref) instrument consisting of four domains, individual domain and overall scores were compiled; and analysed using appropriate statistical techniques. Results: The mean WHOQOL-BREF score for a total of 145 study participants was 46.6±3 with highest score for environmental domain (49.1±4.7) and least for physical domain (44.0±5.2). Significant higher overall quality of life score was observed for comparatively younger participants, males, more educated individuals, those having a companion prior to the settlement, those having more satisfaction with facilities and lesser morbidities. Conclusions: Considering increasing elderly population proportion, there is a need for increase in number of facilities with standardized infrastructure, staff and facilities; so that quality of life can be maintained and sustained. Being a vulnerable and deprived section of the society, it is imperative that such individuals live out the final stage of their life with quality, dignity and much neglected self-respect.